2016
DOI: 10.1007/s40620-016-0271-z
|View full text |Cite|
|
Sign up to set email alerts
|

Podocyturia is significantly elevated in untreated vs treated Fabry adult patients

Abstract: Patients with Fabry disease display heavy podocyturia; those untreated present significantly higher podocyturia, lower proteinuria and better renal function than those who are treated, suggesting that therapy may be started at advanced stages. Podocyturia may antedate proteinuria, and enzyme therapy may protect against podocyte loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 39 publications
3
51
0
1
Order By: Relevance
“…Trimarchi et al . reported greater podocyturia in ERT-naive adult Fabry patients compared to those on ERT; [15] however, the ERT-naïve patients in this study had lower proteinuria and higher GFR than those receiving ERT, indicative of less severe nephropathy in the ERT-naïve patients. In contrast, in the current study, where ERT-naïve and ERT-receiving patients were not different in age, proteinuria, albuminuria or eGFR and thus had more comparable nephropathy, there was no statistical difference in podocyturia between the groups.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Trimarchi et al . reported greater podocyturia in ERT-naive adult Fabry patients compared to those on ERT; [15] however, the ERT-naïve patients in this study had lower proteinuria and higher GFR than those receiving ERT, indicative of less severe nephropathy in the ERT-naïve patients. In contrast, in the current study, where ERT-naïve and ERT-receiving patients were not different in age, proteinuria, albuminuria or eGFR and thus had more comparable nephropathy, there was no statistical difference in podocyturia between the groups.…”
Section: Discussionmentioning
confidence: 61%
“…found increased podocyturia in Fabry patients, but with no correlation between urine podocyte density and either proteinuria or eGFR. [15] In contrast, Pereira et al found correlation between podocyturia and UACR in Fabry patients. [22] The findings of the current study are consistent with Pereira et al with direct correlations between podocyturia and proteinuria in both male and female patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The main manifestations are pathological albuminuria and decreased GFR, although tubular dysfunction may also occur [29]. Moreover, podocyturia, a biomarker suggestive of early kidney involvement, is elevated in FD patients [30,31]. According to studies from the Fabry Registry and the Fabry Outcome Survey, kidney involvement is usually less severe and later among female patients, as observed for other organs [25,32].…”
Section: Discussionmentioning
confidence: 99%